CHALLENGES FACING STRATEGIC IMPLEMENTATION OF COUNTY INTERGRATED DEVELOPMENT PLANS AMONG COUNTY GOVERNMENTS IN KENYA: A CASE OF BARINGO COUNTY - KIPKOECH, KIBOR SAMMY (IJRDO - Journal of Business Management, 2019)
Successful strategy implementation depends on working with and through others, building and strengthening competitive capabilities, motivating and rewarding people in a strategy supportive manner and instilling the discipline of getting things done. The county government came up with a five year term strategic plan called County integrated development plans (CIDPs). The development of CIDP is in congruent with Kenya’s vision 2030, which is the country’s development blueprint. The study’s overall objective was to assess the challenges encountered in the strategic implementation of CIDP in Baringo County; determine the influence of internal conflicts on the strategic implementation of CIDPs; find out how stakeholder involvement influences the strategic implementation of CIDP, to establish the influence of resource allocation on strategic implementation of CIDP and to determine how political situation influences the strategic implementation of CIDPs in Baringo County. Two theories of strategic implementation namely the Chandler’s Strategy-Structure Proposition and The McKinsey’s 7s Model were reviewed to form the theoretical framework of the study. The study adopted the descriptive research design. The target population was 10 CECs, 45 MCAs, 15 Chief Officers and 18 Heads of Departments. The table recommended by Kathuri and Pals was used to select 73 respondents. Stratified random sampling was applied to select 8 CECs, 37 MCAs, 12 Chief Officers and 15 Heads of Departments to constitute the sample size of the study. Primary data was collected via questionnaires. The researcher consulted the supervisors who helped refine the research instrument and to ensure the instrument was valid. A pilot study was conducted to ensure that the instrument was reliable. Descriptive and inferential statistics were employed in data analysis. The study revealed that stakeholder involvement, resource allocation, internal conflicts and political situation accounted for 64.48% of the total variance in strategic implementation of the CIDP. Hence, the study concluded that 27.4% of strategic implementation of the CIDP in the county government of Baringo was explained by internal conflicts, 30.3% by stakeholder involvement, 21.5% by resource allocation and 20.1% by political situation. Therefore, the highest influence was explained by stakeholder involvement, followed by internal conflicts, resource allocation and finally political situation. The study recommended timely management intervention on challenges critically affecting implementation of the strategic implementation of CIDP. The management teams should also be empowered to provide quick response to emerging issues that challenge the implementation of the CIDP. This study would help counties to strategically implement their respective CIDPs after ascertaining the kind of challenges which face the implementation process.